2016
DOI: 10.1017/s136898001600224x
|View full text |Cite
|
Sign up to set email alerts
|

Association between high-risk fertility behaviours and the likelihood of chronic undernutrition and anaemia among married Bangladeshi women of reproductive age

Abstract: Maternal high-risk fertility behaviours are shockingly frequent practices among women in Bangladesh. High-risk fertility behaviours are important predictors of the increased likelihood of women's chronic undernutrition, anaemia and the coexistence of anaemia and undernutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 26 publications
(34 reference statements)
7
41
0
Order By: Relevance
“…The current study highlighted the significant burden of high-risk fertility behavior on anemia occurrence among Ethiopian women. These findings were consistent with a Bangladeshi study, reporting an association between high-risk fertility behaviors and women's nutritional disadvantages [13]. Several mechanisms through which high-risk fertility behaviors could be related to increased likelihood for anemia have been identified previously [28][29][30][31][32].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The current study highlighted the significant burden of high-risk fertility behavior on anemia occurrence among Ethiopian women. These findings were consistent with a Bangladeshi study, reporting an association between high-risk fertility behaviors and women's nutritional disadvantages [13]. Several mechanisms through which high-risk fertility behaviors could be related to increased likelihood for anemia have been identified previously [28][29][30][31][32].…”
Section: Resultssupporting
confidence: 91%
“…The majority of studies have assessed a subset of maternal high-risk fertility behavior individually. A few studies analyzed outcomes associated with the combined influence of maternal high-risk fertility behaviors [13,14]. Yet, such studies are limited in the African context.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that risky fertility behavior is the most pressing health issue in the LMICs considered as a significant cause of neonatal and under-five mortality [5,6]. High-risk fertility behaviors (HRFBs) can be expressed in terms of too-early or too-late women's age at delivery, shorter birth interval, and a higher number of live births [7,8]. High-risk pregnancies have severe ramifications on childhood mortality [5,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A study from Ethiopia indicated a higher risk of under-five mortality associated with high-risk fertility behaviors, especially amongst women aged 15 to 18 years having a high ratio of continuous pregnancies, and shorter birth spacing [14]. Bangladesh Demographic and Health Survey (DHS) report showed that 41.8 % of women evinced a high risk of fertility behaviors, out of which 33% and 8.8% had single HRFB and possessed multiple HRFB, respectively [8]. The prevalence of teenage pregnancies in South Asian countries is high, as women are typically married at a younger age.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, iron intakes were estimated based on food consumption and did not consider iron provided by groundwater. A study has shown that groundwater could provide significant amounts of iron to women in rural areas of Bangladesh [ 30 ]. Therefore, for women living in rural areas of Bangladesh, the levels fortification should be defined taking into consideration of the amounts of iron taken from groundwater, and consequently the decision to fortify both wheat flour and rice with iron or only a single food vehicle should be based on the actual gap between iron intakes from all sources and needs.…”
Section: Discussionmentioning
confidence: 99%